Virtual art therapy : research and practice - Winkel, Michelle; Bodenbender, Christel; Yue, Melissa (Routledge, 2022)
"This book provides a practical, research-based, and innovative exploration of virtual art psychotherapy, documenting how virtual art therapy and its innovations are breaking new ground in the mental health field. Drawing findings from the innovative Virtual Art Therapy Clinic (VATC), chapters present examples, strategies, and experiences delivering quality arts-based therapeutic services and online training. Clinical practice examples support and provide evidence for the transition from in-person to virtual, videoconference-based sessions. Leaders in the art therapy field provide chapters documenting their own research on various facets of the revolution in creative arts therapies online, and in digital media innovations. By combining the collected knowledge, recent learning, and research findings with the expertise of all the contributing authors, this book encourages art therapists to support the further growth in the field of digital art therapy"--